Role of G protein-coupled receptor 120 in respiratory diseases - ZHAO Yanyan, ZHANG Lijun, ZHANG Xiaochun, LIANG Xiangyan, ZHAO Yufeng (Jichu yixue yu linchuang)
G protein-coupled receptor 120 (GPR120) is one of the membrane receptors for long chain free fatty acids and is distributed in alveolus macrophages and airway epithelial Club cells. GPR120 activation alleviates the inflammation of respiratory tract, improves airway hyper-responsiveness, stimulates proliferation of Club cells and promotes the repair of respiratory epithelium, which may attenuate asthma and acute lung injury.